Criminology lead us not into temptation ([United States]: [s.n.)
This film explores the need to look at criminal justice problems in new and different ways than ever before and to devise better and more innovative techniques in the future to keep citizens from becoming criminals.
Converted into VHS 1/2 in. and DVD.
Keywords: Crime and criminals